AKTIVITAS ANTIDIABETES KOMBINASI EKSTRAK LABU KUNING DAN BROTOWALI SECARA IN VIVO - Cikra Ikhda Nur Hamida Safitri; Misbahatul Khoiriyah (Jurnal Medical Laboratory, 2024)
Cucurbita Moschata are rich in polyphenolic antioxidants such as flavonoids which can be used to lower blood sugar levels. Cucurbita Moschata can be formulated into biscuits. The aim is to determine the activity of cucurbita moschata and tinospora crispa extracts on reducing blood sugar in mice (Mus muculus). The research aims to create a Cucurbita Moschata biscuit formula that contains high levels of resistant starch and beta carotene but has the lowest impact on increasing blood sugar levels. This research method is experimental by making an antidiabetic formulation in mice. Mice were divided into normal groups, K groups (CMC NA 1%), groups with varying doses of 100 mg/kg, 300 mg/kg and 600 mg/kg, and positive groups (glibenclamide 0.65 mg/kg). Using the two way anova analysis method. The results showed the effect of reducing blood sugar levels in mice at doses of 100mg/kg (17.3%), 300mg/kg (29.3%), 600 mg/kg (35.2%) and the positive group (44.3%). The 600mg/kg group (35.2%) provided the highest reduction in blood sugar levels, which was close to positive (44.3%) compared to doses of 100mg/kg (17.3%), 300 mg/kg (29.3%). The conclusion of this study is that anti-diabetes biscuits, a combination cucurbita moschata and tinospora crispa , have antihyperglycemic activity in vivo.